2002
DOI: 10.1007/bf03343977
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb alactic anaerobic power output assessed with different techniques in morbid obesity

Abstract: Short-term alactic anaerobic performance in jumping (5 consecutive jumps with maximal effort), sprint running (8 m) and stair climbing (modified Margaria test) were measured in 75 obese subjects (BMI: 40.3+/-5.0 kg/m2) and in 36 lean control subjects (BMI: 22.4+/-3.2 kg/m2) of the same age and gender distribution. The results show that obese subjects attained a significantly lower specific (per unit body mass) power output both in jumping (W(spec,j); p<0.001) and stair climbing (W(spec,s); p<0.001) and run at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 20 publications
6
49
0
Order By: Relevance
“…VJHs in our study were lower than those reported in nonobese children and adolescents 24 ; this is in agreement with the previous studies in obese adolescents 27 and adults, 39 and well explained by the discrepancy between the small difference in lower limb muscle masses between normal and obese adolescents on the one hand and the major overload to be brought up by the obese subjects on the other. VJH increased with age and pubertal development in both sexes and were generally higher in boys than in girls.…”
Section: Anaerobic Aptitudessupporting
confidence: 93%
“…VJHs in our study were lower than those reported in nonobese children and adolescents 24 ; this is in agreement with the previous studies in obese adolescents 27 and adults, 39 and well explained by the discrepancy between the small difference in lower limb muscle masses between normal and obese adolescents on the one hand and the major overload to be brought up by the obese subjects on the other. VJH increased with age and pubertal development in both sexes and were generally higher in boys than in girls.…”
Section: Anaerobic Aptitudessupporting
confidence: 93%
“…W per unit body weight, which represents the actual correlate of the anaerobic performance also in obese subjects, 10 female subjects appear to be at a greater disadvantage for effect of the degree of obesity, the major limitations being suffered by older individuals with higher BMI.…”
Section: Muscular Power Output In Obesitymentioning
confidence: 99%
“…In spite of the motor limitation experienced by extremely obese subjects, mainly due to the hampering effect of fat excess and the poor physical conditioning, a modified SCT has been shown to be a reliable indicator of available power in lower limb muscles, also in these kind of subjects, 10 and has been widely employed on the clinical ground to evaluate the effectiveness of body weight reduction programmes based on physical activity for the improvement of muscle performance and motor coordination. [11][12][13] In the obese individuals of the present study, maximal voluntary lower limb power output was relatively constant up to a certain age (the peak value being displayed by subjects of both genders in the third decade) and then steadily decreased thereafter at the rate of about 1.5-1.6% per year, as it can be seen in Figure 1.…”
Section: Muscular Power Output In Obesitymentioning
confidence: 99%
See 2 more Smart Citations